Modelo de Gestión del Talento Humano para la Compañía Sion Inteligentes SAS (2020)
This research aimed to design a human talent management model for the company Sion Inteligentes SAS, to fill the absence of a flexible and effective human talent management model adjusted to the objectives of the organization and that provides answers to the required skills. It begins with a diagnosis of the current situation of Human Resource management, analyzing the history and environments of Sion Inteligentes SAS. From the collection of this information, the company's Human Talent Management Model was formulated, which includes the recruitment, selection, performance evaluation, training and retention processes, with the aim of forming the appropriate work team to the needs of the company, guaranteeing its long-term tenure, not only due to the economic salary and custom, but also based on emotional compensation and personal growth, which allows the achievement of the organizational objectives set by Sion Inteligentes SAS